Managing Cross-Border Movement of People and Goods in the European Union on the Example of the Road Border Crossing in Lubelskie Voivodship - Witkowski, Piotr (Regional Barometer. Analyses & Prognoses, 2018)
The external border of the European Union is the subject of integrated management aimed at minimizing the risks associated with the illegal movement of people and goods. A significant section of the EU external border is located in the Lubelskie Voivodship. Its length and size of cross-border movement of people and trading goods and the diversification of border infrastructure is significant. The aim of the article is to discuss issues related to the integrated management of EU external borders and to present and analyse border service systems at road border crossing points, divided into a terminal system (Koroszczyn–Kukuryki ) and a so-called “pipe system” (Dorohusk ).